2020
DOI: 10.1093/ehjci/ehaa946.2938
|View full text |Cite
|
Sign up to set email alerts
|

Independent relevance of left ventricular hypertrophy for risk of ischaemic heart disease in 25,000 Chinese adults

Abstract: Background The prevalence of left ventricular hypertrophy (LVH) is strongly related with established cardiovascular disease (CVD) risk factors and, hence, there has been some uncertainty about its independent relevance for ischaemic heart disease (IHD) after taking account of such risk factors. Purpose To examine the associations of LVH with prevalent and incident cases of IHD after adjustment for established risk factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…This study and our previous works showed that the combination of ECG and HRV parameters has the best diagnostic value [30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study and our previous works showed that the combination of ECG and HRV parameters has the best diagnostic value [30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 67%
“…Conversely, when the repolarization pattern becomes fragmented, the relative value of the smaller vectors increases proportionally. Such an approach allows a comparison between the morphology of the T-wave across the 12 leads and the quanti cation of T-wave abnormalities in an observer-independent way [35].…”
Section: Discussionmentioning
confidence: 99%
“…The suggested scaling method was invented precisely for solving practical problems and already has widespread applications [12][13][14] in solving various tasks in different areas of clinical medicine, sports medicine, and large-scale population studies, including the analysis of large ECG data arrays of the Oxford Population Health study.…”
Section: Ecg and Heart Rate Variability Scaling Methodsmentioning
confidence: 99%
“…Запропонований метод шкалювання винайдений саме для вирішення практичних задач і вже знаходить досить широке застосування в Україні та за кордоном [18][19][20][21] для вирішення низки різноманітних завдань у різних розділах клінічної, спортивної медицини, медицини праці, а також у масштабних популяційних дослідженнях [22]. Метод шкалювання ЕКГ, що розроблено, застосовується і при аналізі великого масиву електрокардіографічних даних у рамках дослідження Інституту популяційного здоров'я Університету Оксфорда [23].…”
Section: принципи інноваційної методики шкалювання електрокардіограми та варіабельності ритму серця для виявлення малих змінunclassified